The information industry is a study of its concept, origins and development | صناعة المعلومات دراسة في المفهوم والنشأة والتطور - Al salem | السالم, Salem mohammad | سالم محمد (King Fahad National Library | مكتبة الملك فهد الوطنية, 2024)
Information has now become an industry or a national wealth, like other natural, human, industrial, agricultural, and other wealth that society enjoys. In fact, information is considered the vital artery of contemporary life, and the main pillar for decision-making politically, socially, militarily, and socially. | اصبحت المعلومات في الوقت الراهن صناعة أو ثروة وطنية شأنها شأن الثروات الأخرى التي ينعم بها المجتمع من طبيعية وبشرية وصناعية وزراعية وغيرها، بل إن المعلومات تـعد بمثابة الشريان الحيوي للحياة المعاصرة، والدعامة الرئيسة لصنع القرار سياسياً واجتماعياً وعسكرياً واجتماعياً